Peningkatan stabilitas oksidatif pada minyak kedelai dalam mempertahankan kualitas minyak goreng pada penggorengan berulang: Improving oxidative stability of soybean oil by addition of cardamom essential oils (Elettaria cardamomum) during repeated frying process - Kurniawati, Ajeng Dyah; Latifasari, Nurul; Budiarly, Dias Feby; Arlian, Fitranaya; Lu’lu, Akmel (TEKNOLOGI PANGAN : Media Informasi dan Komunikasi Ilmiah Teknologi Pertanian, 2024)
Frying is a food processing process that is important due to flavor formation in food product. An oxidation reaction shall occur during frying, which may affect the quality and stability of cooking oil. Synthetic antioxidants that exceed this limit can be harmful to health, so in order to enhance the stability of frying oil it is necessary to use of natural antioxidant like phenolic compounds from cardamom essential oil. Thus, this research aims to study the effect of cardamom essential oil addition to the frying oil to enhance its oxidative stability during repeated frying process. This study begins with the characterization of antioxidant activity of cardamom oil including total phenolic content, total flavonoid content, and free radical scavenging ability (IC50). The research was continued by heating soybean frying oil to which various concentration antioxidants have been added, such as 5%, 10%, and 15% for 1 and 3 cycles frying process and the quality of frying oil at before and after processing was analyzed, which includes acid number and peroxide value. The results showed that the total content of phenolic compound levels in cardamom oil was 56.32 ± 2.04 mg GAE/gram; total flavonoids were 40.10 ± 11.66 mg QE/gram; and the IC50 value was 501.37 ppm. The addition of cardamom oil as a natural antioxidant with concentrations of 5%, 10%, and 15% can significantly increase the oxidative stability of soybean oil. The highest increase in the oxidative stability of soybean oil was obtained from the addition of cardamom essential oil at a concentration of 15%.